A systematic review of the evidence on peer education programmes for promoting the sexual and reproductive health of young people in India. Issue 1 (1st January 2020) - Siddiqui, Mariam; Kataria, Ishu; Watson, Katherine; Chandra-Mouli, Venkatraman
Abstract: In the context of a growing adolescent population globally, it is imperative to understand which interventions will most effectively advance their sexual and reproductive health (SRH). In India and globally, peer education is often utilised as an intervention for promoting the SRH of young people. Globally, the evidence of its effectiveness is mixed. A systematic review of the literature from the Indian context gave insight into the knowledge, attitudinal, and behavioural (KAB) outcomes affected by peer education, as well as the inputs, coverage, content, and context of such interventions. Out of the over 1500 publications initially identified through the database and bibliographic searches, 13 were included in the review; no quality assessment was done, given the dearth of publications matching the inclusion criteria. Analysis of the included publications highlights the multiple ways that peer education is implemented in the Indian context, as part of multi-component programmes and as a stand-alone intervention. The KAB outcomes from these initiatives are mixed, with some multi-component and some stand-alone initiatives affecting statistically significant outcomes and others not–a finding consistent with global literature reviewed for this paper. Despite the mixed results and the limited effects of behaviour relative to knowledge, this paper proposes that peer education has a place in an overall response to improving the SRH of young people. It calls for better research on peer education in India, and for research in relation to the optimal conditions for peer education to succeed in affecting KAB and other outcomes.